Monitoring of Trans-resveratrol during Embryogenic Structures Induction in Cotton (Gossypium hirsutum L.) - Hilaire, Kouakou Tanoh; Dramane, Kone; Laurent, N’cho Achi; Bertin, Yao Koffi; Pierre, Teguo Waffo; Alain, Decendit; Jean-Michel, Merillon (Research Aspects in Biological Science Vol. 6, 2022)
Trans-resveratrol is a phytoalexin generated by various plants, including certain grapes. This phenolic compound drew much interest since research suggested that it could be linked to fungi and diseases resistance. Phenolic compounds may be crucial in somatic embryogenesis induction of of various plants. In cell suspension cultures of cotton embryogenic structures form, researchers have long been very concerned about the requirement for biochemical indicators for the early identification of cells able of undergoing to conversion in embryogenic structures. This study aimed at showing link between trans-resveratrol and the induction of embryogenic structures in cotton cell suspension cultures. Both cotton cultivars, Coker 312 and R405-200, were compared in cell suspension culture for their ability to induce somatic embryogenesis. In addition, polyphenols qualitative analysis by HPLC was performed to identify trans-resveratrol in each cultivar (Coker 312 and R405-200) freeze-dried cells. Results showed that only trans-resveratrol appeared in Coker 312 embryogenic cell suspensions. This phenolic compound started producing at the first subculture (2.44 \(μ\)g/g dw) and the maximum level was reached at the third subculture (7.20 \(μ\)g/g dw) with an increase of nearly 295%. This study demonstrated link between the embryogenic structures stimulation and the trans-resveratrol production in cotton cells. Trans-Resveratrol may constitute phenolic marker for cotton somatic embryogenesis induction.